Efficacy of chemical and flourescent protein markers in studying plant colonization by endophytic nonpathogenic Fusarium oxysporum isolates - Paparu, P.; Macleod, A.; Dubois, T.; Coyne, Danny L.; Viljoen, Altus (2009)
In studying plant colonization by inoculated Fusarium oxysporum endophytes, it is important to be able to distinguish inoculated isolates from saprophytic strains. In the current study, F. oxysporum isolates were transformed with the green (GFP) and red fluorescent protein (DsRed) genes, and benomyl- and chlorate-resistant mutant isolates were also developed. The benomyl- and chlorate-resistant mutants, and the fluorescently labelled transformants, were able to grow on potato dextrose agar amended with 20 mg Benlate® l−1, 30 g chlorate l−1 and 150 μg hygromycin ml−1, respectively. Single spores of all mutants remained stable after several transfers on non-selective media. Most mutants and transformants produced colony diameters that did not differ significantly from that of their wild-type progenitors after 7 days of growth on non-selective media. Few mutants, however, had growth rates that were either slower or faster than for their wild-types. Plant colonization studies showed that root and rhizome tissue colonization by most benomyl- and chlorate-resistant mutants was similar to that of their wild-type isolates. Unlike GFP transformants, DsRed transformants were difficult to visualize in planta. Both the mutants and transformants can be used for future studies to investigate colonization, distribution and survival of biocontrol F. oxysporum endophytes in banana plants.